2011
DOI: 10.1155/2011/947138
|View full text |Cite
|
Sign up to set email alerts
|

Electroacupuncture-Induced Cholinergic Nerve Activation Enhances the Hypoglycemic Effect of Exogenous Insulin in a Rat Model of Streptozotocin-Induced Diabetes

Abstract: The aim of this study is to explore the mechanisms by which electroacupuncture (EA) enhances the hypoglycemic effect of exogenous insulin in a streptozotocin- (STZ-) diabetic rats. Animals in the EA group were anesthetized and subjected to the insulin challenge test (ICT) and EA for 60 minutes. In the control group, rats were subjected to the same treatment with the exception of EA stimulation. Blood samples were drawn to measure changes in plasma glucose, free fatty acids (FFA), and insulin levels. Western bl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
15
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 17 publications
2
15
0
Order By: Relevance
“…That is to say, this combined therapy seems to have the potential benefit of extending the time before pancreatic beta cell failure occurs with type 2 diabetic patients rather than improving insulin resistance. This result is compatible with our previous studies that have shown that insulin sensitivity is enhanced by EA stimulation at the bilateral Zusanli acupoints of normal male Wistar rats and of streptozotocin induced diabetic rats when evaluated by the HOMA index [12, 13]. Furthermore, in another study on the effect of EA on insulin sensitivity among steroid background male Wistar rats, the EA group rats were found to also exhibit lower HOMA indices compared to the non-EA group rats [27].…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…That is to say, this combined therapy seems to have the potential benefit of extending the time before pancreatic beta cell failure occurs with type 2 diabetic patients rather than improving insulin resistance. This result is compatible with our previous studies that have shown that insulin sensitivity is enhanced by EA stimulation at the bilateral Zusanli acupoints of normal male Wistar rats and of streptozotocin induced diabetic rats when evaluated by the HOMA index [12, 13]. Furthermore, in another study on the effect of EA on insulin sensitivity among steroid background male Wistar rats, the EA group rats were found to also exhibit lower HOMA indices compared to the non-EA group rats [27].…”
Section: Discussionsupporting
confidence: 93%
“…In addition, studies have shown that EA (15 Hz) at the Zusanli acupoint treatment is able to induce a hypoglycemic response in streptozotocin induced diabetic rats by stimulating the cholinergic nerves, which in turn stimulate the expression of insulin signaling proteins [32]. Additionally, the action of EA has a combined effect that involves both cholinergic nerve stimulation and increased nNOS activity via a lowering of the plasma FFA concentration; the result is enhanced glucose tolerance as described in our recently published reports [13, 27, 33, 34]. Taking the above findings as a whole, we were therefore interested in the role of FFA and how it influences insulin activity when diabetic patients are treated using the combination therapy.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…A single large dose of streptozotocin-induced rat model of type-1 diabetes mellitus was used in the present study (19,20). By virtue of direct toxic effects of streptozotocin, as in human type 1 diabetes, immune destruction plays a role in inducing insulinopenic diabetes.…”
Section: Discussionmentioning
confidence: 99%
“…Low‐frequency EA lowers plasma glucose and increases plasma insulin in normal and type 2 diabetic rats, but not in type 1 diabetic rats, and it can therefore be considered insulin dependent (5, 10). However, the increased response to exogenous insulin after electrical stimulation seen in both types 1 and 2 diabetic rats indicates an insulin‐sensitizing effect (43, 44), possibly mediated by increased GLUT4 concentrations in muscle and adipose tissue (10, 44).…”
Section: Discussionmentioning
confidence: 99%